2017
DOI: 10.4088/jcp.15m10479
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Cardiometabolic Status in Youth With Early-Onset Psychosis

Abstract: ClinicalTrials.gov identifier: NCT01119014; European Clinical Trials Database (EudraCT): 2009-016715-38​​​.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…Age, gender, race, parental education, and lifetime nicotine use were considered as potential covariates based on group differences in our sample and prior research. 46 Age, gender, and parental education were significantly associated with at least one of the metabolic variables and were included as covariates. Additionally, prior clinically significant second-generation antipsychotic use (i.e., ≥3 months) was examined as a covariate because of the known association with weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, gender, race, parental education, and lifetime nicotine use were considered as potential covariates based on group differences in our sample and prior research. 46 Age, gender, and parental education were significantly associated with at least one of the metabolic variables and were included as covariates. Additionally, prior clinically significant second-generation antipsychotic use (i.e., ≥3 months) was examined as a covariate because of the known association with weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression models were used to examine group differences on the binary metabolic variables. Age, gender, race, parental education, and lifetime nicotine use were considered as potential covariates based on group differences in our sample and prior research . Age, gender, and parental education were significantly associated with at least one of the metabolic variables and were included as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Similar findings were found in youth through the recent Tolerability and Efficacy of Antipsychotics (TEA) trial. Drug-naïve first-episode psychosis patients ages 12–17 years had higher waist circumference, total cholesterol, LDL, and non-HDL levels compared to controls (Jensen et al, 2017 ). These suggestions have been challenged in meta-analyses that exclude patients with affective psychosis (which could lead to confounding changes in dietary or exercise habits).…”
Section: Contemporary Evidence Of Intrinsic Metabolic Risk In Schizopmentioning
confidence: 99%
“…36 The study on early-onset psychosis conducted on teenage population by Jensen et al also indicated that elevated metabolic risk with dyslipidemia may be present even prior to pharmacotherapy. 37 There are some limitations in this study that need to be discussed. The sample of our study was limited to 20 PWS patients and 18 DGS patients due to the rarity of the syndromes as well as exclusion of patients with lower levels of intellectual functioning.…”
Section: Discussionmentioning
confidence: 94%